Using Question & Answer Forums as a Platform for Improving Transport-Related Information for Tourists. (September 2020) - Gal-Tzur, Ayelet; Bar-Lev, Shirly; Shiftan, Yoram
Providing relevant, complete, and coherent information to travelers wishing to get from one destination to another is a fundamental responsibility of transport authorities. This study explored the characteristics of information desired by tourists seeking travel instructions through Question & Answer forums, particularly TripAdvisor's city forums, with the aim of developing guidelines to improve answers. Three categories of travel information were defined, and a scenario-based survey was conducted among 558 tourists. Based on its results, a novel multidimensional model for assessing the quality of information posted in response to questions was developed. The study yielded several main conclusions. Shorter answers of up to four information items are preferred over longer ones, and diverse information types are preferred over several of the same category. Given an accurate basic existing answer, our model suggests that information should be added only when one or more of the three information categories is not already represented.